2015
DOI: 10.1007/s12029-015-9696-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Iranian Colorectal Cancer Patients at Risk for Lynch Syndrome: a New Molecular, Clinicopathological Feature

Abstract: A different molecular and clinicopathological phenotype of tumors in CRC Iranian patients at risk for Lynch syndrome could suggest some new molecular mechanisms about which more evaluations are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…6,15 The 5 markers were also used in our center, and it is of note that both BAT25 and BAT26 were unstable in all MSI-H tumors in our present cohort, similar to the previous studies. [7][8][9] Therefore, care should be taken before scoring a MSI-H tumor with stable BAT25 or BAT26; samples mix-up must be first excluded. Given the high frequency of BAT26-unstable tumors, one study suggested that BAT26 may be used for the initial MSI screening in sporadic CRCs in regions with limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…6,15 The 5 markers were also used in our center, and it is of note that both BAT25 and BAT26 were unstable in all MSI-H tumors in our present cohort, similar to the previous studies. [7][8][9] Therefore, care should be taken before scoring a MSI-H tumor with stable BAT25 or BAT26; samples mix-up must be first excluded. Given the high frequency of BAT26-unstable tumors, one study suggested that BAT26 may be used for the initial MSI screening in sporadic CRCs in regions with limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there are at least three main molecular pathways underlying the development of colorectal cancer (CRC): Chromosomal instability (CIN) pathway, microsatellite instability (MSI) pathway, and CpG island methylator phenotype (CIMP) pathway. [ 1 2 3 ] CIN is the most prevalent molecular cause of genomic instability in CRC, so it is an original genetic basis of about 65%–70% of all sporadic CRC tumors. [ 4 ] CIN is characterized with an imbalance in number of chromosomes (aneuploidy), chromosomal amplification, and a high frequency of loss of heterozygosity resulting in some deleterious mutations in tumor suppressor genes such as APC and TP53 , and oncogenes including KRAS .…”
Section: What Are Molecular Pathways Behind Colorectal Cancer?mentioning
confidence: 99%
“…MSI is a particular molecular change as a hallmark of averagely 15% of CRCs. [ 3 9 ] At first, these molecular changes were named “dispersed somatic mutations” in simple tandem repeats[ 13 ] or a replication error phenotype (RER). [ 14 ] Due to a defect in DNA-mismatch repair (MMR) system, microsatellites or short tandem repeats, repetitive sequences containing 1–6 nucleotide units up to 100 times, are prone to accumulation of mutations.…”
Section: What Is Microsatellite Instability?mentioning
confidence: 99%
“…The basic tests identify five markers (NR-21, BAT-26, BA T -25, NR-27 and NR-24) to devise the simplest diagnostic assay (9). Previous reports have shown significant diversity regarding the most common marker for microsatellite testing; BAT 25, BAT26 and NR21 have been reported in HNPCC and sporadic CRCs (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Table 1 shows the reports from Iran that studied the frequency of MMR genes in both hereditary and sporadic colorectal cancers.…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%
“…Table 1 shows the reports from Iran that studied the frequency of MMR genes in both hereditary and sporadic colorectal cancers. As it shows, the frequency of MSI in patients with HNPCC has been 29% -62.5% (9-25), there are not so many studies about the frequency of MSI in sporadic CRC from Iran; however, the reported frequencies of MMR have been from 19.4% to 66.6% (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%